Air flow distribution and cooling performance on modular cold storage for fishery commodity - Muhammad Arif Budiyanto; Oktandio Imamudien; Arnas Lubis; Muhammad Idrus Alhamid; Takeshi Shinoda (Energy Reports, 2023)
Cold storage plays a vital role in the supply chain of fishery products. Efficient cold storage design is a future challenge for developing regions with limited energy supplies. This paper aims to analyze the cooling performance and airflow distribution of modular cold storage. Modular cold storage is designed with a size of 20 ft for remote areas with the main cargo of fishery products. The analysis used empirical equations and numerical simulations of fluid flow and heat transfer. Variation of cooling load and inlet air velocity was conducted to investigate the cargo’s cooling distribution and cooling speed. To achieve the desired product temperature inside cold storage rooms have obtained different cooling times. The optimum cooling time in the anteroom is 5 h and in air-blast freezer room is 3.5 h with an inlet air velocity setting is 8 m/s both, while the optimum cooling time in the freezer room is 6 h with an inlet air velocity setting is 2 m/s. Furthermore, the results of this paper also offer recommendations for pre-cooling fish products to minimize excessive cooling in air-blast freezer room.